Fifty years of Rietveld refinement: Methodology and guidelines in superconductors and functional magnetic nanoadsorbents - Flores-Cano, Diego A. (2021)
The Rietveld refinement method has taken high relevance since its creation. Nowadays, it is an useful tool in many fields of industry, materials science, and technology. For these reasons, it becomes a need for scientists and engineers whom pretend to use it for proper analysis of their materials. However, the initiation in the method can be slow, taking into account the accelerated rhythm of the research and economic demands. Thus, this work is an intend to fulfill this hole, providing the basic foundations and methodology of the Rietveld refinement in a brief way, this along with the results of its application in superconducting samples of Yttrium Barium Copper Oxide and magnesium diboride, and functional magnetic nanoadsorbents of maghemite and a multiphasic composite (iron oxide, hydroxyapatite and secondary phases). In the process, an in-detail protocol was designed and provided. It was concluded that the samples were successfully refined and that this work represents a fast introduction to the Rietveld method for which beginners can obtain good results while making correct interpretations ofthe whole refinement process.